Aspectos epidemiológicos, clínicos, morfológicos, histomorfométricos e mensuração tecidual dos níveis de cobre na intoxicação espontânea por cobre em bovinos de corte - Martins, Kamila Peruchi Fernandes (2022)
Copper is an essential trace mineral, which when in excess can induce hepatic necrosis, hemolytic anemia, hemoglobinuric nephrosis that can result in the death of cattle. The aim of this study is (1) to describe the epidemiological, clinical and anatomopathological aspects of an outbreak of copper poisoning in cattle; and (2) to describe the histological and histomorphometric hepatic alterations of the disease in intoxicated cattle and with a subclinical picture, comparing with a group of control cattle. The outbreak occurred in semi-confined cattle after supplementation with 50mg/kg of copper in dry matter with the death of 35 cattle. Necropsy was performed on 20 animals and the most frequent macroscopic alterations were jaundice, enlarged liver with an evident lobular pattern, kidneys and urinary bladder contents of brownish to blackish color. Microscopically, in the liver there was vacuolar degeneration and/or zonal, centrilobular or paracentral hepatocellular coagulative necrosis. In the kidneys, vacuolar or hyaline degeneration and coagulative necrosis of the tubular epithelium were noted, as well as intratubular hemoglobin casts. The copper levels detected in the liver and kidney were 5901.24 to 28373.14µmol/kg and 303.72 to 14021µmol/kg respectively. The study of the morphological and histomorphometric aspects describe the qualitative and quantitative differences of hepatocellular alterations between the three compared groups: cattle that presented clinical disease (GD), subclinical (GSC) and a control group (CG). Copper values in liver dry matter (DM) ranged from 720 to 1019 um/Cu/g in GSC; from 498 to 1803 µm/Cu/g in the DG and from 299 to 418 µm/Cu/g in the GC. In liver samples, it was observed that degenerative changes and random necrosis were predominant in GSC and centrilobular necrosis in DG. The GC hepatocytes were larger and had a centralized and spherical nucleus. These parameters changed in a decreasing way in GSC and DG with smaller hepatocytes, with nuclear deviation and irregularity of the nuclear contour with all statistically significant values (p<0.001). It is possible to conclude that bovines with more than 500µg/Cu/g MS present, when sick, the predominance of centrilobular necrosis and when subclinical, degeneration and random hepatocellular necrosis. These alterations, histomorphometrically, were demonstrated by the decrease and irregularity of the hepatocyte contour according to the evolution of intoxication.